2003
DOI: 10.1023/a:1025560513308
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The frequency, severity, and outcome of flutamide-induced hepatic injury were prospectively evaluated in 55 patients with prostate cancer who received 125 mg of flutamide 3 times a day (daily dose: 375 mg) combined with an agonistic analogue of luteinizing hormone-releasing hormone. In addition, we examined plasma and urine concentrations of flutamide and its major metabolites 4 weeks after the beginning of flutamide therapy, and evaluated their significance in predicting flutamide-induced hepatic dysfunction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…6) Although it is suggested that flutamide and its toxic metabolites could be responsible for such hepatic injury the mechanism of toxicity remains presently unknown. 6) It is observed that the serum concentration of FLU-1 is higher 3,7) and that of OH-flutamide is lower in patients with liver dysfunction than in those with normal liver function. 11) The formation of OH-flutamide from the parent compound is catalyzed by CYP1A2.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…6) Although it is suggested that flutamide and its toxic metabolites could be responsible for such hepatic injury the mechanism of toxicity remains presently unknown. 6) It is observed that the serum concentration of FLU-1 is higher 3,7) and that of OH-flutamide is lower in patients with liver dysfunction than in those with normal liver function. 11) The formation of OH-flutamide from the parent compound is catalyzed by CYP1A2.…”
mentioning
confidence: 99%
“…The 1 H-NMR data showed close resemblance to those of 1 except for the presence of a two proton singlet due to an amino group at d 5.30. It was identified as 2-methyl-N-[4-amino-3-(trifloromethyl) The short names as per Aizawa et al 7) and Takashima et al 18) publications. …”
mentioning
confidence: 99%
See 3 more Smart Citations